Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

What are the limits of $u_n = u_{n-1}.\frac{n}{n+1}$ and $v_n = v_{n-1}.\frac{n+1}{n}$ ?

Seems that $u_n \to 0$ and $v_n \to \infty$, but I can't prove it.

  1. For $u_n$ we have an infinite product of term all strictly lower than $1$. Can we say that goes to 0, and why ?
  2. For $v_n$ we have an infinite product of teram all strictly greater than $1$. Can we say that goes to infinity, and why ?

Edit : by induction, $u_n = \frac{u_{1}}{n+1}$ and $v_n = v_{1}.({n+1})$. and thus the result.

But does 1. and 2. are valid statements (Maybe I need to open an other question?).

share|cite|improve this question
Regarding your for u/v questions: Both assumptions are false in general, common counter-examples are can be found on $\prod\limits_p (1-p^{-2})^{-1}=\zeta(2)$ has factors strictly $>1$ and $\prod\limits_p (1+p^{-2})^{-1}=\zeta(4)/\zeta(2)$ has factors strictly $<1$. – gammatester Oct 28 '13 at 13:01
There is absolutely no need to consider these as infinite products and, in my opinion, it only clouds the issue by introducing a lot of unnecessary machinery – TBrendle Oct 28 '13 at 13:02

Hint: Just write out $u(n)$ and $v(n)$ for $n \le 5$ or $n \le 10$, say.

Prove your conjectures for closed forms for $u(n)$ and $v(n)$ by induction.

Now the limits should be easy.

For your conjectures, consider the following identities:

$$1 = \sin\frac{\pi}2 = \frac\pi2\prod_{n=1}^\infty \left(1-\frac1{4n^2}\right)\qquad \sinh \frac\pi2 = \frac\pi2\prod_{n=1}^\infty\left(1+\frac1{4n^2}\right)$$

which demonstrate that such infinite products may converge to nontrivial values (for which a necessary condition is that the individual terms converge to $1$).

See the Wikipedia lemma for more information.

share|cite|improve this answer
Question edited for induction – Timmy Oct 28 '13 at 12:53
@Timmy Yes, that's correct. I've added a bit on infinite products. – Lord_Farin Oct 28 '13 at 12:55

The question is not well posed, since you didn't specify initial points. Fortunately, convergence of the first sequence doesn't depend on its initial point.

You have $$ u_n = u_{n-1}\frac{n}{n+1}. $$ Then also $$ u_{n+1} = u_{n} \frac{n+1}{n+2}. $$ Combining these facts, we have $$ u_{n+1} = u_{n-1}\frac{n}{n+2}. $$ Show by induction that $$ u_{n+k} = u_{n-1} \frac{n}{n+k+1}. $$ Then since $$ \lim_{k \to \infty} \frac{n}{n+k+1}=0, $$ we have $u_{n+k} \to 0$ as $k \to \infty$. This implies $u_n \to 0$ as $n \to \infty$.

The behavior of the other sequence will depend on the initial point $v_0$. If $v_0<0$ then it diverges to $-\infty$, if positive then to positive infinity, and if $v_0=0$ then the sequence converges trivially to 0. Since you didn't specify an initial point, just a recurrence relation, we have no way to decide.

share|cite|improve this answer

Fix $u_0$ and $v_0$ as any arbitrary numbers. The idea that follows is independent of the values ​​that $u_0$ and $v_0$ assume. $$ \begin{array}{rcl} u_n&=& u_{0}\frac{1}{1+1}\cdot\frac{2}{2+1}\cdot\cdot\frac{3}{3+1}\cdot \ldots\cdot\frac{(n-1)}{(n-1)+1} \cdot\frac{n}{n+1}\\ u_n&=& u_{0}\frac{1}{2}\cdot\frac{2}{3}\cdot\cdot\frac{3}{4}\cdot \ldots\cdot\frac{(n-2)}{n-1}\cdot\frac{(n-1)}{n} \cdot\frac{n}{n+1}\\ &=& u_{0}\frac{1}{n+1}\longrightarrow 0\\ \end{array} $$ So we entirely analogous $$ v_n=v_0\cdot \frac{2}{1}\cdot\frac{3}{2}\cdot\cdot\frac{4}{2}\cdot \ldots\cdot\frac{(n-1)}{n-2}\cdot\frac{(n-2)}{n-1} \cdot\frac{n-1}{n+1}\cdot \cdot\frac{n}{n+1}\\ =v_0\cdot(n+1)\longrightarrow \mbox{sgn}(u_0)\infty, \quad\mbox{ if } v_0\neq 0. $$ In general if the product is a telescopic product ( exemple $\prod_{k=1}^n\frac{f(k)}{f(k-1)}=\frac{f(n)}{f(0)}$ ) and there is $\lim_{k\to \infty}\frac{f(n)}{f(0)}=L\in\mathbb{R}\cup\{-\infty,+\infty\}$ then $$ x_n= \begin{cases} x_0,& \mbox{ if } n=0\\ \prod_{k=1}^n\frac{f(k)}{f(k-1)}x_0,& \mbox{ if } n>0\\ \end{cases} \implies \lim_{n\to\infty}x_n=L\cdot x_0 $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.